2002
DOI: 10.1161/01.cir.0000040587.73251.48
|View full text |Cite
|
Sign up to set email alerts
|

Response to Adenosine Differentiates Focal From Macroreentrant Atrial Tachycardia

Abstract: Background-We previously proposed that adenosine has mechanism-specific effects on atrial tachycardia (AT), such that adenosine terminates AT attributable to triggered activity, transiently suppresses automatic rhythms, and has no effect on macroreentrant AT. This, however, remains controversial, because other studies have reported that adenosine terminates reentrant AT. To clarify this issue, we used 3D electroanatomic mapping to delineate the tachycardia circuit and thereby determine whether the response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 22 publications
1
77
1
Order By: Relevance
“…4 However, other investigators have reported divergent findings, reporting that adenosine also terminates macroreentrant AT, thus suggesting that termination of AT with adenosine is a nonspecific finding, which does not identify tachycardia mechanism. [5][6][7] In light of the challenges of demonstrating entrainment in microreentant AT and of the conflicting data with respect to the mechanistic effects of adenosine in AT, we sought to develop a discriminatory algorithm that could obviate the limitations and ambiguities of overdrive pacing enumerated above and introduce Algorithm for Atrial Tachycardia a methodology that could rapidly distinguish between macroreentrant and focal AT and, more particularly, differentiate microeentrant AT from focal AT caused by triggered activity or automaticity.…”
Section: See Editorial By Chughmentioning
confidence: 99%
“…4 However, other investigators have reported divergent findings, reporting that adenosine also terminates macroreentrant AT, thus suggesting that termination of AT with adenosine is a nonspecific finding, which does not identify tachycardia mechanism. [5][6][7] In light of the challenges of demonstrating entrainment in microreentant AT and of the conflicting data with respect to the mechanistic effects of adenosine in AT, we sought to develop a discriminatory algorithm that could obviate the limitations and ambiguities of overdrive pacing enumerated above and introduce Algorithm for Atrial Tachycardia a methodology that could rapidly distinguish between macroreentrant and focal AT and, more particularly, differentiate microeentrant AT from focal AT caused by triggered activity or automaticity.…”
Section: See Editorial By Chughmentioning
confidence: 99%
“…1 On the other hand, Iwai et al examined the response of 43 patients with AT to adenosine and reported that all focal AT were terminated by rapid injection of adenosine, except for those whose etiologies were due to macroreentry. 20 More recently, based on electrophysiological behavior and response to drugs, they suggested that para-Hisian AT was mechanistically consistent with triggered activity. 2 Further investigation is needed to elucidate the mechanism of this type of AT.…”
Section: Electrophysiological Characteristicsmentioning
confidence: 99%
“…The published studies involved a limited number of patients, 7 to 120. Focal tachycardias in the right atrium are ablatable with success rate >90% (Kottkamp H et al, 1997;Marchlinski F et al, 1998;Iwai S et al, 2002). The same success rate may be achieved in macroreentrant atrial tachycardia related to post-surgical scar (Iwai S et al, 2002).…”
Section: Left Atrial Tachycardiamentioning
confidence: 99%
“…Focal tachycardias in the right atrium are ablatable with success rate >90% (Kottkamp H et al, 1997;Marchlinski F et al, 1998;Iwai S et al, 2002). The same success rate may be achieved in macroreentrant atrial tachycardia related to post-surgical scar (Iwai S et al, 2002). In the left atrium, focal tachycardias were localized to mitral annulus, roof, posterior wall, appendage and septum (Dong J et al, 2005).…”
Section: Left Atrial Tachycardiamentioning
confidence: 99%
See 1 more Smart Citation